Risky Decision-Making but Not Delay Discounting Improves during Inpatient Treatment of Polysubstance Dependent Alcoholics - De Wilde, Bieke; Bechara, Antoine; Sabbe, Bernard; Hulstijn, Wouter; Dom, Geert (Frontiers in Psychiatry, 2013)
Background: High levels of impulsivity, characteristics of addicted patients, are known to be important predictors of relapse. However, so far, little is known about the stability or variability of two main components of impulsivity (delay discounting and decision making). The present study examined the changes in impulsivity during the first week of an abstinence based, behavioral orientated inpatient treatment program. Method: 37 polysubstance dependent alcoholics completed the Delay Discounting Task (DDT), and the Iowa Gambling Task (IGT) using the original version with decks A’B’C’D’, and an alternative version with decks K’L’M’N’, for measuring decision making, after two and six weeks of active treatment. Results: It was found that performances on the IGT changed during treatment while performances on the Delay Discounting Task did not (test-retest period: 4 weeks). Conclusions: The results provide preliminary evidence that improvements in decision making might be related to treatment effects. All patients followed a highly structured cognitive-behavioral treatment program, which might have enhanced their executive functioning (coping skills training).